Navigating the AI tide: challenges, opportunities, and future directions for early-career dermatologists - Zhang, Meng; Chu, Ruiqi; Liu, Chunmei; Zhang, Shengni; Ren, Xiangxiang (Frontiers in Medicine, 2025)
Artificial intelligence (AI) has demonstrated diagnostic accuracy comparable to dermatologists in specific tasks (e.g., 92.5% vs. 86.6% for melanoma detection in multicenter trials), while significantly outperforming early-career physicians (15–20% higher accuracy in meta-analyses). This review synthesizes evidence on AI’s transformative impact on dermatology training and practice, addressing critical gaps in ethical frameworks and implementation strategies. We propose a competency-based framework for “AI-augmented dermatology,” advocating for curriculum integration of AI literacy modules, standardized human-AI workflows, and proactive engagement in regulatory processes. Early-career dermatologists must leverage AI as a safety net while strengthening irreplaceable skills in complex decision-making and patient communication to lead dermatology’s AI-integrated future.